The Effects of Task-Based Animated Movies on EFL Students’ Listening and Speaking Skills: A Quasi-Experimental Study - Serly Amanda; Miranti Eka Putri (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aimed to determine the effect of using animated films integrated with task-based activities on students’ listening and speaking skills at SMP Muhammadiyah 1 Pekanbaru. A quantitative method with a quasi-experimental pre-test and post-test control group design was employed. The participants were 56 seventh-grade students selected through purposive sampling, consisting of 28 students in the experimental class and 28 students in the control class. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, homogeneity test, and independent samples t-test with the aid of IBM SPSS Statistics 27. The results showed that the experimental class achieved higher post-test mean scores than the control class in both listening (87.50 vs. 73.21) and speaking (77.68 vs. 71.25). The mean gain in listening was 26.43 points in the experimental class compared with 16.25 points in the control class, while the mean gain in speaking was 26.61 points compared with 20.36 points, respectively. The independent samples t-test revealed significant differences in listening skills (p = 0.000) and speaking skills (p = 0.009). Furthermore, the estimated Cohen’s d effect sizes were 1.20 for listening and 0.72 for speaking, indicating large and medium-to-large effects, respectively. These findings demonstrate that integrating animated films with task-based activities can effectively improve students’ listening and speaking skills in EFL instruction.